Urteilen lernen / [1] Grundlegung und Kontexte ethischer Urteilsbildung / Ingrid Schoberth (Hg.) - Schoberth, Ingrid (Urteilen lernen, 2012)
Correctly judging situations plays a large role in everyday life – it´s not always easy to determine the right thing to do, and only then can one actually do the right thing: properly deciding between two or more possible alternatives.This volume shows the necessity of making a scientific analysis of the various ways of reaching ethical competence. It demonstrates the various forms and nature of judgment within a scientific-theological and interdisciplinary research context, having resulted from a common discourse of Christian and Jewish theology as well as jurisprudence. The basic questions are discussed and compared to the perspective about learning to judge that is not innate: Moral education demands positive and workable paths in which children and adolescents as well as adults can practice executing proper judgement. For this reason a number of example contexts with an ethical background – in education, worklife and the legal system – are examined in detail.
... Tagungsreihe ... , aus der der vorliegende Band hervorgegangen ist. ... Die Ergebnisse der ersten beiden Tagungen, die 2010 und 2011 in Heidelberg stattgefunden haben, werden nun in diesem Sammelband veröffentlicht. - Seite 10
Keywords: Aufsatzsammlung; Konferenzschrift; Urteilen; Ethikunterricht; Religionspädagogik; Christliche Ethik; Theologische Ethik; Sittliche Erziehung